Seven key initiatives for preventing a recurring food crisis - Fan, Shenggen (2011)
Taken from IFPRI Policy Brief 16 "Urgent Action Needed to Prevent Recurring Food Crises" by Shenggen Fan, Maximo Torero, and Derek Headey (March 2011)